From Chitin to Bioactive Chitooligosaccharides and Conjugates: Access to Lipochitooligosaccharides and the TMG‐chitotriomycin1. Issue 44 (11th September 2014) - Despras, Guillaume; Alix, Aurélien; Urban, Dominique; Vauzeilles, Boris; Beau, Jean‐Marie
Abstract The direct and chemoselective N‐transacylation of peracetylated chitooligosaccharides (COSs), readily obtained from chitin, to give per‐N‐trifluoroacetyl derivatives offers an attractive route to size‐defined COSs and derived glycoconjugates. It involves the use of various acceptor building blocks and trifluoromethyl oxazoline dimer donors prepared with efficiency and highly reactive in 1, 2‐trans glycosylation reactions. This method was applied to the preparation of the important symbiotic glycolipids which are highly active on plants and to the TMG‐chitotriomycin, a potent and specific inhibitor of insect, fungal, and bacterial N‐acetylglucosaminidases.